LITERASI KESIAPSIAGAAN DALAM MENGANTISIPASI BENCANA SOSIAL DI LINGKUNGAN MASYARAKAT KUMUH - HARIFUDDIN, HARIFUDDIN; MAIDIN, RUSDI; NONCI, NURMI (Arunika: Jurnal Pengabdian Masyarakat, 2024)
The social conditions of people in slum neighbourhoods are full of irregularities such as messy living arrangements, and chaotic physical environment, and the lives of the residents are not healthy either. Such social conditions which is a fertile ground for the growth of social problems that lead to criminality, social to criminality, social problems such as quarrels, fights, noise and commotion that have the potential to become social disasters. Whereas, the on the other hand, slum communities want a quiet life and Therefore Therefore, this service was held which aims to: (1) equip the community with knowledge about the importance of preparedness in facing social threats in slum neighbourhoods. (2) equip the community with skills to handle social threats in their neighbourhood. Social threats that occur in their neighbourhood. This service occurred in Makassar City, precisely in Buntusu Village, Tamalanrea District. The activity took the form of literacy consisting of socialisation and training. The participants are residents living in the slum area representing each sub-district as evidenced by a letter from the head of each sub-district. 4 training participants represented each sub-district. Makassar City has 15 sub-districts with a total population of 1,432,189 people. Training participants as well as respondents totalled 160 people who were selected using the Slovin method. After the socialisation and training, all participants were given a questionnaire to determine their level of knowledge and skills in receiving the material presented by the presenters.